FEATURES OF THE CLINIC AND DIAGNOSIS OF CROHN'S DISEASE IN CHILDREN AT THE PRESENT STAGE (World Science, 2022)
Based on a retrospective analysis of case histories, the article presents modern data on the features of the clinical course of Crohn's disease in childhood, laboratory, endoscopic and morphological markers of the disease. The symptomatology of Crohn's disease is described in the onset and in the period of the developed clinical picture, depending on the localization of the inflammatory process.